5G large-scale array antenna technology development and innovation direction - Shengjun LUO; Shenke ZHANG (Dianxin kexue)
In view of the current system architecture and technical solutions of 5G large-scale antennas,new technological developments and innovation directions were proposed,including low profile and light weight radiation element,high precision amplitude and phase calibration networks,all-in-one dense radiation arrays,and highly integrated antenna without reflection,antenna integrated filter,antenna and filter common module,mechanical phase shift and digital shaping combined,5G dual-band antenna,4G ＆amp; 5G intelligent antenna,etc.For each technological innovation direction,an overview and useful description were given.